(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف هذا البحث إلى تعرّف العلاقة بين العوامل الخمسة الكبرى في الشخصية والتوافق الزواجي لدى عينة من الأزواج في محافظة دمشق، وتعرف الفروق في كل من العوامل الخمسة الكبرى في الشخصية والتوافق الزواجي تبعاً لمتغيري الجنس وعدد سنوات الزواج لدى أفراد العينة نفسها. وتكونت عينة البحث من 300 زوج وزوجة من هذه المحافظة، واستخدم الباحث مقياس التوافق الزواجي وقائمة العوامل الخمسة الكبرى في الشخصية، وذلك لدراسة العلاقة بين هذين المتغيرين وتعرّف الفروق، وقد استخدمت فيه القوانين الإحصائية (معامل الارتباط بيرسون، ت ستيودنت)، وأظهرت النتائج وجود علاقة ارتباطية بين التوافق الزواجي وبين كل من عامل الانبساطية وحيوية الضمير والعصابية، ولا توجد علاقة ارتباطية بين التوافق الزواجي وبين كل من عاملي الطيبة والتفتح، ووجود فروق في التوافق الزواجي تبعا لمتغير الجنس، وأنه لا فروق في التوافق الزواجي تبعا لمتغير عدد سنوات الزواج. وتوجد فروق في كل من العوامل الكبرى في الشخصية عدا عامل التفتح وذلك تبعاً لمتغير الجنس، ولا توجد فروق في كل من العوامل الكبرى في الشخصية عدا عامل الطيبة وذلك تبعاً لمتغير عدد سنوات الزواج. This research aimed to identify the relationship between the five big factors of personality and the martial parallel among a sample of chapels in Damascus, and to identify the differences inthe five big factors of personality and the martial parallel according to gender and years of marriage. The sample consists of 300 chapels from Damascus, and the researcher used martial parallel questionnaire and between the five big factors of personality questionnaire to study the relationship between the two variables, and T student and person correlation was used. The findings showed that there is a relationship betweenthe martial parallel and Extraversion, Conscientiousness, and Neuroticism, and there is no relationship between martial parallel and Agreeableness and Opennessto Experience, and there are differences inmartial parallel according to gender. However, there are no differences in martial parallel according to years of marriage, and there are differences infive big factors of personality exceptOpenness to Experience factor according to gender, and there are differences in five big factors of personality except Agreeableness factor according to years of marriage.